The Choice of Monetary and Exchange Rate Arrangements for a Small, Open, Low-Income Economy The Case of Sao tome and Principe - Wang, Jian-Ye (International Monetary Fund, 2008)
This paper assesses São Tomé and Príncipe''s monetary and exchange rate arrangements in light of the country''s monetary history and the relevant experience of comparable countries in Africa. The study highlights several structural characteristics of São Tomé and Príncipe including its very small size, high degree of openness, extensive use of foreign currencies, and inflexible product and factor markets in the consideration of an appropriate monetary and exchange regime. Firmly anchored currency arrangements, defined in this paper to include memberships in monetary unions or hard pegs, are found to be preferable to the status quo of a managed float. The paper applies statistical methods and takes into account other factors to identify the appropriate anchor currency. It stresses that fiscal discipline and prudent debt management are the main prerequisites for a firmly anchored currency arrangement